Pengaruh Peran Kepemimpinan terhadap Keberlanjutan Pelayanan Publik: Studi pada Dinas Kependudukan dan Pencatatan Sipil Kota Padang - Rona Atmasyih Hutasoit; Boni Saputra (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2025)
The sustainability of public services has become a strategic issue in the era of digital transformation, as the implementation of the SiRancak digital service at the Population and Civil Registration Office (Disdukcapil) of Padang City still faces challenges such as server outages, slow document processing, and a lack of system integration, thereby requiring strong leadership to ensure its sustainability. This study aims to analyze the influence of leadership roles on the sustainability of public services at the Padang City Disdukcapil. The study employed an associative quantitative approach involving 42 employees selected from a population of 70 via simple random sampling, with the sample size determined using the Slovin formula. A validated instrument measuring six indicators of leadership roles and three indicators of service sustainability was used, and the data were analyzed using simple linear regression with SPSS 25. The results indicate that both leadership roles and the sustainability of public services fall into the “very good” category (TCR 85.53% and 87.33%), with the regression equation Y = 23.456 + 0.417X, t-calculated = 2.713 > t-table = 2.021, and significance 0.010 (p < 0.05), as well as a coefficient of determination R² = 0.509. These findings underscore the importance of strengthening monitoring functions and a sense of service ownership at the Padang City Population and Civil Registration Office (Disdukcapil) to ensure the effective and adaptive sustainability of population administration services.